An unusual cause of febrile hepatitis. (25th June 2015) - Stelzer, Teresa; Kohler, Sibylle; Marques Maggio, Ewerton; Heuss, Ludwig Theodor
Abstract : We describe the case of a 51-year-old man with recently diagnosed ulcerative colitis who developed fever and elevated liver enzymes as well as cholestasis a few weeks after starting treatment with mesalazine. As no obvious cause was found and fever persisted, liver biopsy was performed and revealed granulomatous hepatitis. The patient recovered completely after cessation of mesalazine, so that a drug-induced granulomatous hepatitis after exclusion of other differential diagnoses in an extensive work up was assumed. The present case demonstrates that even though drug-induced liver injury due to mesalazine is rare, it should be considered in unclear cases and lead to prompt discontinuation of mesalazine.